Methane production and energy balance in Murrah buffalo heifers fed on complete diets of different composition - SARASWATI, M L; HAQUE, N; SENGAR, S S; TOMAR, S K (The Indian Journal of Animal Sciences, 2014)
Murrah buffalo heifers (12) weighing 350 kg, about 2-year-old, divided into 3 groups of 4 animals each, were fed on isonitrogenous complete feeds (mash) having similar roughage: concentrate ratio with various sources of nitrogen (oil cakes), group 1 (wheat straw 40%, molasses 10%, rice bran 27%, deoiled mustard-cake 20%, mineral mixture 2% and common salt 1%), and group 2 (wheat straw 40%, molasses 10%, rice bran 23%, deoiled mustard-cake 12%, deoiled sunflower-cake 12%, mineral mixture 2% and common salt 1 %), and group 3 (wheat straw 40%, molasses 8%, rice bran 39%, deolied soybean-cake 10%, mineral mixture 2% and common salt 1 %). Animals in all the groups were also offered 2 kg green sorghum separately. Dry matter intake was not statistically different in 3 groups. The digestibility of dry matter and other nutrients was similar in all the 3 groups. The GE, DE and ME intakes were similar in all groups. Methane energy loss as percentage ofGE, DE and ME in all the 3 groups were also similar. Methane production per kg digestible OM was not significantly different in three groups. The energy balance was 49.7±5.93, 46.7±5.40 and 40.5±1 0.86 kcal/kg W/d in groups 1,2 and 3, respectively, showing no significant difference among the groups. The animals in all groups were in positive nitrogen balance. It is concluded that sources of nitrogen (olicakes) have no effect on methane production and energy balance in buffalo in isonitrogenous diets.